O imaginário residual no conto de fadas Coraline, de Neil Gaiman - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Fairies, witches, princesses, warriors, monsters and magic are some of the most prominent elements when it comes to fairytales, narratives made popular by the European tradition that survived through time and spaces, merging with tales from another cultures, from another lands, influencing and being influenced by other mentalities, according to Roberto Pontes. The believe in entities that comes to surface in those stories builds a series of complex structures that Pontes refers to as imageries, the matter of this paper. Tolkien (2010) is my main reference in the matter of fairytales, nonetheless the theories of names such as Bettelheim (1980), Propp (2001), Carter (2012), Coelho (2012), and Todorov (2013) are also heavily considered in the study of Coraline (2004), by English author Neil Gaiman, as a fairytale, a resulting from the gathering of many imageries, from a diverse range of residual folktale elements retold by the contemporary literary craft that infuses such mix with new meanings. The analysis is here made through specific categories from which residual lines are drawn, offering a large range of reading possibilities over the text of Gaiman.
Keywords: Literatura comparada; Contos; Contos de fadas na literatura; LINGUISTICA, LETRAS E ARTES: LETRAS: LITERATURA COMPARADA; Imaginário; Residualidade; Contos de fadas; Contos populares; Neil Gaiman